ANALISIS FATWA DSN-MUI NO. 25/DSN-MUI/2002 TENTANG PELELANGAN BARANG DI PEGADAIAN SYARIAH - Popon Srisusilawati; Anisa Fitria; Selly Eriska; Tiara Deasy Nurfitriani Sumarwan; Nendiarti Juniar (el-Jizya: Jurnal Ekonomi Islam, 2021)
In Islam, pawning is known as Ar-rahn, which is to make an item as collateral for debt, provided that if there is difficulty in payment, the debt can be paid from the sale of the goods used as collateral. In sharia pawnshops, the auction system applies to customers, if the customer is unable to redeem the pawned goods and pay their debts after maturity. An auction is an attempt to repay loans that cannot be repaid to a certain extent. Auctions according to sharia must also be accountable for Islamic law, which is free from elements of gharar, maisir, usury and falsehood. The auction mechanism in sharia pawnshops is regulated in the second part of the General Provisions for Fatwa DSN No.25 / DSN-MUI / 2002, point 5 concerning auction. The purpose of this research is to find out whether the sharia auction mechanism is in accordance with the fatwa or not. The method used in this writing is qualitative descriptive. The result of this research is that the sharia embedding mechanism is in accordance with the DSN-MUI Fatwa No. 25 / DSN-MUI / 2002 concerning Auctions.